Strategi ‘Meminta Maaf’ Anak Usia Pra-Sekolah di Lembaga Pendidikan daQukids Semarang - Ririn Setyowati (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this research is to show the use of apologizing acts strategies by TK B Al-A’la students in daQukids educational institution of Semarang who are average five-year-old, in which they are the subjects of this research. Three steps in doing this research are stated. Firstly, prepare the data which consists of data collection. Data collection is done by a method named ‘simak’. Simak’s method is carried out by using Simak Bebas Libat Cakap technique (SBLC) in which it is done by recording and then transcribing. Conversational classification is based on the use of apologizing strategies by Al-A’la students. Secondly is data analysis by using the method of Padan Pragmatics to know apologizing acts from speaker to hearer. Thirdly, researcher presents the result of the analysis through the description of the data that have been analyzed. From the research, it is found that six strategies of apologizing acts are used, they are the first strategies namely opting-out, second is evasive strategies, the third strategies is indirect apologies, the forth strategies is direct apologies, the fifth strategies is remedial support and the last is apologies as strategic disarmers.